Intergovernmental Transfers Reduction Policy and Flypaper Effect: Case of Covid-19 Pandemic in Indonesia - Sherlita Nurosidah; Mohamad Khusaini; Ferry Prasetyia (Universitas Negeri Malang, 2023)
This study empirically examines the influence of intergovernmental transfers and the fall of it to local government’s expenditure in Indonesia as well as the possibility of flypaper effect occurrence over pandemic. Over the years, in general, intergovernmental transfers in Indonesia was increasing since decentralization was applied in 2000 till the pandemic hit the country which made the regulator for the first time in 20 years decided to cut overall transfers for municipalities in order to recover economically. A set of cross-section data used in this study is the year 2020 from 34 provinces, 417 regencies, dan 91 cities. The result of pooled OLS regression model shows that flypaper effect does appear for all types of expenditures, such as total expenditure, capital expenditure, and operational expenditure of the local government. Asymmetric response of those three are quite varied. Total expenditure shows asymmetry whereas capital and operational expenditures find the opposite.